The evaluation of project-based learning in Malaysia: propose a new framework for polytechnics system - Sadrina sadrina; Ramlee Mustapha; Muhammad Ichsan (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
Technical and Vocational Education is one of the various disciplines that believed could encourage the country's economic growth. Project-Based Learning or PBL was introduced in the Malaysian polytechnics curriculum in terms to produce creative and innovative graduates Thus, Project-Based Learning was introduced because of the ineffectiveness of the traditional lecture method. This study was a kind of descriptive study intended to examine the perception of students and supervisors regarding the Project-Based Learning at one Polytechnic in Malaysia. A population of 170 would be represented by a sample size of 118 respondents and 43 supervisors to participate in the study. The result found that the significant aspect to be included in Project-Based Learning is effective supervising skills. However, from the data, some supervisors have no proficiency skills of Project-Based Learning. Based on the empirical data which derived from the present study, a new framework for Project-Based Learning is suggested for the polytechnics system.